In silico chromosome staining: Reconstruction of Giemsa bands from the whole human genome sequence - Niimura, Yoshihito (The National Academy of Sciences, 2002)
Giemsa staining has been used for identifying individual human chromosomes. Giemsa-dark and -light bands generally are thought to correspond to GC-poor and GC-rich regions; however, several experiments showed that the correspondence is quite poor. To elucidate the precise relationship between GC content and Giemsa banding patterns, we developed an “in silico chromosome staining” method for reconstructing Giemsa bands computationally from the whole human genome sequence. Here we show that 850-level Giemsa bands are best correlated with the difference in GC content between a local window of 2.5 megabases and a regional window of 9.3 megabases along a chromosome. The correlations are of strong statistical significance for almost all 43 chromosomal arms. Our results clearly show that Giemsa-dark bands are locally GC-poor regions compared with the flanking regions. These findings are consistent with the model that matrix-associated regions, which are known to be AT-rich, are present more densely in Giemsa-dark bands than in -light bands.